Evaluating the Necessity of Routine Pathological Analysis of Pe‑ diatric Adenotonsillectomy Specimens: A Retrospective Study of 9817 Cases - Tekin, Mustafa Said; Kocaoğlu, Emine Hilal; Günay, Celal; Şeneldir, Lütfi (ENT Updates, 2025)
Background: Adenotonsillectomy is commonly performed in children. Pathological evaluation of specimens of patients with or without risk factors is generally performed. Our aim is to indicate that it is not necessary to send all adenotonsillectomy specimens routinely for pathological analysis in pediatric age group. Materials and Method: Patients in the pediatric age group who underwent routine tonsillectomy and/or adenoidectomy (T&A) at a tertiary healthcare center affiliated with XXX University between January 2015 and December 2023 were collected. A retrospective study was designed. The following information was recorded for each included patient: age at surgery, gender, and pathology reports. Demographic and clinical outcomes are reported using means and standard deviations for continuous variables and percentages for categorical variables. Results: Our study of 9817 patients at Medipol University Medipol Mega Hospital revealed no unexpected result in adenotonsillectomy pathology specimens. Conclusions: Our study of 9817 patients at Medipol University Medipol Mega Hospital revealed no unexpected result in adenotonsillectomy pathology specimens. Histopathological analysis may be limited to cases with certain clinical risk factors to protect important healthcare resources in patient care.